Sistema web para gerenciamento de empresas produtoras de eventos - Fonseca, Cicero Raldi da (2013)
Organizing an event takes a lot of information. To manage a social agreements are needed agreements between client and organizer, invoices, protocol. The company that produce events is often responsible for managing the event altogether, thus having to store various information about the event, customers and other aggregated information. Based on the large amount of information to be stored, there is a need to produce management software of these companies. This management refers to the possibility of these companies store all information relating to the event in a centralized database, with security and flexibility to search for the desired information. This work concerns the development of a web based system for managing companies that produce events. The implementation was performed using the Microsoft® Visual Studio 2012 Express, Microsoft ® SQL Server 2012 Express as database, Microsoft ® Visual Basic.NET, JavaScript, and Microsoft® Report Viewer to create reports.